Neuromuscular and torque kinetic changes after 10 months of explosive sport training in prepubertal gymnasts - Kochanowicz, A.; Niespodzinski, B.; Mieszkowski, J.; Sawczyn, S.; Cieszczyk, P.; Kochanowicz, K. (Pediatric Exercise Science, 2019)
To determine neuromuscular and torque kinetic changes after 10 months of explosive sport training in the elbow of prepubertal gymnasts compared with untrained age-matched controls. Methods: In 15 young gymnasts (9.02 [0.41] y) and 15 age-matched untrained males (8.76 [0.51] y), the rate of torque development (RTD) using the Biodex System 4 and the coactivation index were evaluated using electromyography. Explosive strength variables were normalized to the peak torque. Measures were determined twice: before and after a 10-month period of gymnastic training. Covariation analysis was used to account for differences in baseline values between gymnasts and controls. Results: After 10 months of training, gymnasts demonstrated a significantly (P<.05) greater increase in normalized peak RTD values in elbow flexion compared with controls (7.76% vs 0.65%). Covariation analysis also revealed a significantly (P<.05) greater reduction in the coactivation index of elbow extension in the gymnasts (-7.81% [5.44%] points) compared with controls (-1.23% [6.32%] points). Conclusions: Compared with physical development alone, 10 months of explosive-strength training of young gymnasts is sufficient to increase torque-normalized RTD in the elbow joint of prepubertal boys. The RTD changes the authors observed in antagonistic elbow functions vary among gymnasts due to the specific demands of gymnastic training.